The effectiveness of a 6-year oral health education programme for primary schoolchildren - Vanobbergen J, Martens L, Lesaffre E, Bogaerts K, Declerck D (Blackwell Synergy, 2004)
The aim of this study was to evaluate the effect of a 6-year oral health education programme in primary schoolchildren.